Skriti pridih podeželja? - Uršič, Matjaž (Teorija in praksa, 2015)
The article examines the impact of culture and class for the formation of residential preferences in Slovenian cities. The author's method is based on the assumption that the process of urbanisation has close ties with certain forms of socio-cultural development and specific class patterns. The author first explains the historical particularities of the development of Slovenian towns and then, on the basis of existing research studies (e.g. culture and class, values of space and place) analyses the differences between classes in relation to life in the city. The comparison of responses from the two largest Slovenian cities and other parts of Slovenia reveals a complex picture of class characteristics that indicates a very specific relationship towards large cities and a different process of acculturation relative to countries that have big (metropolitan) cities. In this context, it appears that, despite noticeable class distinctions among the respondents, there is a certain common value basis and a strong association with the local environment that promotes residential patterns which are characteristic of less densely populated areas.
Keywords: bivanjski vzorci; Culture; Družbeni razredi; Kultura; Slovenia; Slovenija; Social classes; Urban development; Urban sociology; Urbana sociologija; Urbani razvoj; urbanizacija; vrednote